Peritumoral edema at brain meningiomas - V. A. Byvaltsev; V. A. Sorokovikov; E. B. Borisov; I. A. Stepanov (Acta Biomedica Scientifica, 2016)
Among edema-producing neoplasms of central neural system, the meningiomas are unique. Meningiomas are histologically benign, slow growing and originate extracerebrally. The development of accompanying peritumoral brain edema (PBE) occurs in 40-60 % of meningiomas and often with a high degree of PBE with no obvious relation to the size and histologic features of the meningioma. The aim of our study was to determine the correlation between such parameters as gender, age of the patient, localization of the tumor tissue and the presence/severity of PBE. At meningiomas PBE was present in 70,1 % of patients. Meningioma with the presence of PBE occur more often than tumors without PBE. Olfactory groove tumors have more pronounced degree of PBE, unlike meningiomas of parasagittal localization and the region of the wings of the sphenoid bone. Mixed meningiomas had a greater degree of PBE unlike meningotheliomatozic and fibroblastic variants.